Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng - Duan, Yani; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2017)
Mendozellus paralaredanus sp. n. from Uruguay and M. rakitovi sp. n. from Peru are described. M. asunctia Cheng is redescribed, the ovipositor is illustrated for the first time, and newly recorded from Argentina. M. serratus DeLong is transferred to Haldorus Oman based on the male genitalia structure, creating the new combination H. serratus (DeLong), comb. n. A checklist and key to species of Mendozellus are provided.